Oxygen and carbon isotopes rom the shells of Globorotaloides hexagonus from sediment core TR163-23 - Catherine V Davis (PANGAEA, 2024)
Here we document the stable isotope (δ18O and δ13C) from the shells of planktic foraminifer Globorotaloides hexagonus from Eastern Equatorial Pacific core site TR163-23 (0° 24.6 extquotesingle N, 92° 9.6 extquotesingle W; 2,730 m depth). Morphometric measurements include the length of the shell along the longest dimension from the final chamber, the number of chambers in the final whorl, and porosity. Porosity was assessed by the percentage of surface area on the final chamber consisting of pores. Stable isotope analyses were carried out on pooled samples of 3-10 shells, while morphometrics were measured in individuals.